Women for President : Media Bias in Nine Campaigns - Falk, Erika (Book collections on Project MUSE., 2010)
"Newly updated to examine Hillary Clinton's 2008 presidential campaign, Women for President analyzes the gender bias the media has demonstrated in covering women candidates since the first woman ran for America's highest office in 1872. Tracing the campaigns of nine women who ran for president through 2008 Victoria Woodhull, Belva Lockwood, Margaret Chase Smith, Shirley Chisholm, Patricia Schroeder, Lenora Fulani, Elizabeth Dole, Carol Moseley Braun, and Hillary Clinton - Erika Falk finds little progress in the fair treatment of women candidates." "The press portrays female candidates as unviable, unnatural, and incompetent, and often ignores or belittles women instead of reporting their ideas and intent. This thorough comparison of men's and women's campaigns reveals a worrisome trend of sexism in press coverage - a trend that still persists today."--Jacket.